2006
DOI: 10.1086/499968
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Capsular Serotype K1 ofKlebsiella pneumoniaeCausing Primary Pyogenic Liver Abscess

Abstract: The operon containing magA is responsible for capsular serotype K1 of K. pneumoniae. Several loci in the operon are unique determinants of K1 strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
208
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(225 citation statements)
references
References 36 publications
(37 reference statements)
11
208
0
4
Order By: Relevance
“…Furthermore, molecular serotyping is capable to determine a potential serotype of capsule-deficient isolates (7,18,19). We recommend that PCR analysis could be helpful in seroepidemiologic studies and early-tracing of contingent metastatic infections in patients with liver abscess (7,10,11,(15)(16)(17)(18)(19)(20). This is the first report on the occurrence of serotypes K1 and K2 in the clinical specimens and shows the pathogenic potential of these isolates in different organs.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, molecular serotyping is capable to determine a potential serotype of capsule-deficient isolates (7,18,19). We recommend that PCR analysis could be helpful in seroepidemiologic studies and early-tracing of contingent metastatic infections in patients with liver abscess (7,10,11,(15)(16)(17)(18)(19)(20). This is the first report on the occurrence of serotypes K1 and K2 in the clinical specimens and shows the pathogenic potential of these isolates in different organs.…”
Section: Discussionmentioning
confidence: 89%
“…The present study demonstrates that K. pneumoniae of K1 serotype is mostly responsible for invasive liver abscess increasingly prevalent in Korea as well as in Taiwan. A Taiwanese study has demonstrated a pathogenic role of the magA gene in liver abscess using molecular Koch's postulates, 12 however, magA is now known as a conserved gene in the serotype-specific region of the K1 capsule gene cluster, 11,37 and K1 capsular polysaccharide per se is considered as one of the essential virulence determinants for the development of invasive liver abscess. 37,38 Recently, rmpA-associated hypermucoviscosity phenotype has also been reported to play an important role in invasive purulent diseases caused by K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…A Taiwanese study has demonstrated a pathogenic role of the magA gene in liver abscess using molecular Koch's postulates, 12 however, magA is now known as a conserved gene in the serotype-specific region of the K1 capsule gene cluster, 11,37 and K1 capsular polysaccharide per se is considered as one of the essential virulence determinants for the development of invasive liver abscess. 37,38 Recently, rmpA-associated hypermucoviscosity phenotype has also been reported to play an important role in invasive purulent diseases caused by K. pneumoniae. 39 Global differences in the incidence and clinical patterns of community-acquired invasive infections caused by K. pneumoniae has been addressed by a worldwide collaborative study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, KLAs have also been reported in Western and other Asian countries (Pope et al, 2011). Although the pathogenic mechanism of KLA remains unknown, several virulence traits including K1 capsular polysaccharides (Fung et al, 2002), magA (Chuang et al, 2006), iron acquisition loci on pLVPK (Tang et al, 2010), as well as type 1 and type 3 fimbriae (Struve et al, 2009;Stahlhut et al, 2012) have been implicated with a role in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%